(untitled) (Politeja, 2016)
The evolution of the regional system of cooperation for peace and security in Africa led to the formation of institutionalized methods and forms of cooperation within the framework of regional international organizations (Organization of African Unity, African Union) and the creation of the African Peace and Security Architecture. One of the important forms of activity within it became peacekeeping operations. Maintenance, building and peace enforcement missions have become part of the strategy to shape the international environment in which security is a prerequisite for the smooth implementation of development goals. African international forces heretofore have participated in stabilization operations in countries such as Chad, Rwanda, Burundi, the Comoros, Sudan, Somalia and the Central African Republic.